Vergi hukukunda ayırma prensibi - Yalti, Ayça (My University, 2013)
Ayırma İlkesi, Ayırma Prensibi, Vergi Hukuku, Emek, Sermaye, Vergilendirme ÖZET VERGİ HUKUKUNDA AYIRMA PRENSİBİ Ayırma prensibi güçsüz ve kırılgan olan emeğin, onu elde eden kişiden bağımsız bir şekilde devamlılık arz eden sermaye geliri karşısında korunmasını amaçlayarak, diğer bir deyişle; toplumun güçsüz ve nispeten gelir seviyesi düşük kesimini, gelir seviyesi yüksek kesim karşısında koruyarak sosyal adaletin sağlanmasına hizmet etmektedir. Söz konusu prensibin, sosyal devlet, sosyal adalet ve sosyal adaletin vergilendirmedeki görünümü olan, vergi adaleti bakımından önemi nedeniyle bu konunun incelenmesi ihtiyacı doğmuştur. Tezin birinci bölümünde ayırma prensibinin kuramsal konumu incelendi. İlk kısımda ayırma prensibinin genel bir tanımı yapıldı, ikinci kısımda ayırma prensibine duyulan gereksinim ve prensibin genel seyri incelendi. Takip eden kısımlarda ise, prensibin hukuksal, işlevine değinildi. Günümüz uygulamasında ayırma prensibinin zıt uygulaması olan ikili gelir vergilemesi modeline, -detaylı araştırma bir başka tezin konusu olabilecek derinlikte olduğundan- yalnızca ana hatlarıyla değinildi. İkinci bölümde ayırma prensibinin temellendiği ana prensipler incelendi ve ayırma prensibinin sosyal devlet, sosyal adalet, vergi adaleti ve verginin mali güçle orantılı olmasıyla ilişkisi ortaya kondu. Üçüncü bölümde Türk vergi sisteminde ayırma prensibi incelendi. Daha sonra ayırma prensibi Gelir Vergisi Kanunu bağlamında, ücret kavramı üzerinden, Kurumlar Vergisi Kanunu bağlamında ise, sermaye geliri ve kurum kazancı kavramları üzerinden iki kısımda incelenecektir. ple of discrimination, wages, capital, taxation, tax law.

PRINCIPLE OF DISCRIMINATION ON TAX LAW The purpose of the discrimination principle is the protection of the weak and fragile 'labour' income, regardless of who gains it, against the capital income that is continuous; in other words, it serves for social justice by protecting the powerless and considerably low income part of the society against the high income part. This principle requires an evaluation for its importance in social government, social justice and tax justice that is the reflection of social justice in taxation. The first section of this paper explains the institutional position of the discrimination principle. The first part of this section provides a general description of the discrimination principle while the second part of this section discusses the need for the discrimination principle and its [historic development]. The following parts mention the legal function of the discrimination principle. The paper also briefly discusses the dual taxation principle, the current practice which is the opposite practice of the discrimination principle, in its general terms -given that the dual taxation is a wide concept that can be the subject of a paper in its entirety-. The second section of this paper evaluates the fundamental principles constituting the basis of the discrimination principle and proves the relationship between the discrimination principle and the social government, social justice, tax justice and that the tax shall be rated based on the financial power. The third section of this paper explains the discrimination principle in the Turkish taxation system. The discrimination principle is also be discussed in two parts: in relation to wage within the context of Income Tax Law and also, in relation to capital income and corporate income within the context of Corporate Tax Law.
Keywords: Maliye; Vergi Hukuku; Vergilendirme